1989
DOI: 10.1002/anie.198904831
|View full text |Cite
|
Sign up to set email alerts
|

Radical Anion Salts of Naphthalenetetracarboxylic Acid Derivatives—a Novel Class of Electrically Conducting Compounds

Abstract: The search for new organic conductors has led to a broadly variable class consisting of the radical anion salts of naphthalenetetracarboxylic dianhydride and diimide. The X‐ray structure analysis of the complex 1 (single crystal conductivity σ20°C = 10 S cm−1) revealed a stacking of anionic units characteristic of one‐dimensional conductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…As an interpretation of the UV-VIS and ESR spectra, the authors suggested a charge transfer from the aluminum surface to the NTCDA carbonyl groups. In addition, the broad and red-shifted UV-VIS absorption band suggests an electronic cross talk between neighboring molecules as is typical of excited-and ground-state and anion radical p-aggregates of naphthalene derivatives 14,15,56,57 . The infrared absorption spectrum of NTCDA presents a strong peak at ~1780 cm -1 due to the dianhydride carbonylic group 53 .…”
Section: Ntcda-bayerite Powder Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…As an interpretation of the UV-VIS and ESR spectra, the authors suggested a charge transfer from the aluminum surface to the NTCDA carbonyl groups. In addition, the broad and red-shifted UV-VIS absorption band suggests an electronic cross talk between neighboring molecules as is typical of excited-and ground-state and anion radical p-aggregates of naphthalene derivatives 14,15,56,57 . The infrared absorption spectrum of NTCDA presents a strong peak at ~1780 cm -1 due to the dianhydride carbonylic group 53 .…”
Section: Ntcda-bayerite Powder Characterizationmentioning
confidence: 95%
“…Both reduced species display electronic transitions in the visible region that markedly differ from that of the parent compound. Moreover, crystalline salts based on anion radical salts of naphthalene tetracarboxylic acid derivatives have been prepared for application as electron conducting compounds 14 . Another feature of NTCDA derivatives is their thermal stability that allows thermal treatments up to ~450 °C without chemical or physical decomposition 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, reports have appeared in the recent literature describing the use of 1,4,5,8-naphthalenediimides in Langmuir-Blodgett films (8). conducting materials (9,10), n-stacks of reduced diimide (1 I), nanotubelike structures (1 2). organometallo macrocycles ( 1 3) and models for the photosynthetic reaction center (14).…”
Section: Introduction Todynamic Therapymentioning
confidence: 99%
“…Single-crystal X-ray structural analyses and infrared spectra showed that partial hydrolysis of ntcd lead to the formation of ntcaa during the hydrothermal (7). Symmetry code: D 1 À x, 1/2 + y, Àz À 1/2; E 1 À x, y À 1/2, Àz À 1/2; F 2 À x, Ày À 2, Àz.…”
mentioning
confidence: 98%
“…[1][2][3][4]. Naphthalene-1,4,5,8-tetracarboxylic dianhydride (ntcd), has been employed as starting materials to prepare macrocyclic molecules with large cavity or aromatic p-systems in the study of molecular recognition or electrically conducting materials [5][6][7][8]. However, research has rarely been focused on its coordination chemistry except for a binuclear complex ½Cu II 2 ðntcaaÞ 2 Á 4H 2 O (ntcaa = naphthalene-1,4,5,8-tetra carboxylic acid 4,5-anhydride) reported in 1987 [9].…”
mentioning
confidence: 99%